Integrated nutrient management prescription for late-sown wheat (Triticum aestivum) - MEENA, R B; PANDEY, R N; TRIVEDI, A; CHOBHE, K A; SHARMA, V K; PARIHAR, C M (The Indian Journal of Agricultural Sciences, 2023)
Integrated nutrient management prescription was developed for late-sown variety of wheat (Triticum aestivum L.) (HD 3059) through soil test based crop response study. A field experiment was conducted at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi during winter (rabi) season of 2020–21 and 2021–22 to develop the integrated nutrient management prescription for late-sown wheat. Experiment was laid out in factorial randomized block design with 24 treatments having 3 levels of each N (60,120,180 kg/ha), P2O5 (30, 60, 90 kg/ha) and K2O (20, 40, 60 kg/ha). The basic parameters, viz. nutrient requirement (NR), percentage contribution of nutrients from soil (CS); fertilizer (CF) and farmyard manure (FYM) (CFYM) were quantified. Fertilizer prescription equations in integration with FYM were developed from the data obtained in the study. In order to produce 100 kg of late-sown wheat, the amount of major nutrients needed were 2.24 and 2.27, 0.45 and 0.47, 1.89 and 1.92 kg of nitrogen (N), phosphorus (P) and potassium (K) during 2020–21 and 2021–22, respectively. Phosphorus as soil nutrient contributed the maximum towards crop production; while the contribution of K from fertilizer (118.38 and 125.03) was highest for both seasons. Contribution of N from fertilizer (50.05, 51.38) was more than that of soil (33.81, 33.65). However, contribution of all the nutrients from FYM was lower. The equations developed were used to formulate ready reckoner for a range of soil test values to get a yield target of 55 q/ha for late-sown wheat. Nutrient management of late-sown wheat involving inorganic fertilizer in integration with FYM (10 t/ha) was prescribed through the ready reckoner. The study suggests that the excessive amount of fertilizer consumption as well as the subsequent adverse effect on the environment can be curtailed if FYM is used in combination with inorganic fertilizer.